2017
DOI: 10.1017/s1041610217001211
|View full text |Cite
|
Sign up to set email alerts
|

Costs and quality of life in community-dwelling patients with Alzheimer's disease in Spain: results from the GERAS II observational study

Abstract: Societal costs associated with AD in Spain were largely attributable to caregiver informal care costs and increased with increasing AD dementia severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 28 publications
6
50
0
Order By: Relevance
“…This trend is consistent with previous reports examining AD severity and costs regardless of the method used to define AD severity and of the country where the study was conducted [35][36][37][38][39]. In GERAS-J, patient direct medical costs remained relatively constant across AD severity groups, consistent with GERAS-I [20] and GERAS-II (Spain) [22]. Our multivariate analyses showed a common pattern of independent factors associated with total societal costs among Japan and EU countries.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This trend is consistent with previous reports examining AD severity and costs regardless of the method used to define AD severity and of the country where the study was conducted [35][36][37][38][39]. In GERAS-J, patient direct medical costs remained relatively constant across AD severity groups, consistent with GERAS-I [20] and GERAS-II (Spain) [22]. Our multivariate analyses showed a common pattern of independent factors associated with total societal costs among Japan and EU countries.…”
Section: Discussionsupporting
confidence: 90%
“…The key results presented here are consistent with baseline results from GERAS-I (UK, France, and Germany) [20] and GERAS-II (Spain) [22]. The total societal costs associated with AD in GERAS-J rose with increasing AD severity and were approximately 1.9-fold higher among patients with moderately severe/severe than with mild AD.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Recent studies have shown that the overall point prevalence of dementia due to AD among individuals older than 60 years is over 40 per 1000 persons (2). The disease affects society both in terms of economy and of quality of life (3). Despite the use of many different treatments, there is currently no effective way to halt the progression of the disease (4–8).…”
Section: Introductionmentioning
confidence: 99%